Endothelial dysfunction is an independent risk factor for stroke patients irrespective of the presence of patent foramen ovale - KEPEZ, ALPER; ÖZBEN SADIÇ, BESTE; MİDİ, İPEK; SÜNBÜL, MURAT (URBAN & VOGEL, 2013)
Paradoxical embolization through the patent foramen ovale (PFO) is the major cause of most cryptogenic stroke cases. However, the presence of PFO may simply be an incidental finding in these patients, and endothelial dysfunction may be the underlying reason of ischemic stroke. The aim of this study was to compare the endothelial function of cryptogenic stroke patients according to the presence of PFO. Sixty consecutive patients with cryptogenic stroke referred for transesophageal echocardiography (TEE) and 39 consecutive nonstroke patients referred for TEE examination because of suspected PFO were included in the study. Endothelial functions were assessed by brachial artery ultrasonography. PFO was diagnosed by the presence of right-to-left passage of contrast bubbles during TEE. Stroke and nonstroke patients were further subdivided into two groups according to the presence of PFO. Stroke patients had significantly lower flow-mediated dilation (FMD) values than nonstroke patients (8.36 +/- 4.38 % vs. 12.57 +/- 4.90 %, p < 0.001). The stroke patients with PFO had significantly lower FMD measures than nonstroke patients with PFO (6.60 +/- 3.98 % vs. 10.84 +/- 4.40 %, p = 0.001). Similarly, cryptogenic stroke patients without PFO had significantly lower FMD measures than nonstroke patients without PFO (9.90 +/- 4.18 % vs. 14.22 +/- 4.88, p = 0.002). Logistic regression analysis showed FMD as an independent predictor of cryptogenic stroke when adjusted by age, sex, and presence of PFO (odds ratio: 0.809, 95 % confidence interval: 0.719-0.911, p < 0.001). An FMD value of 11.30 % or lower predicted cryptogenic stroke with a sensitivity of 78.3 %, a specificity of 66.7 %, and positive and negative predictive values of 78.3 and 66.7 %, respectively. Endothelial dysfunction seems to play a more important role than PFO in the underlying mechanism of cryptogenic stroke.
Keywords: Endothelial function; Patent foramen ovale; Stroke; Risk factor; Transesophageal echocardiography; FLOW-MEDIATED VASODILATION; CRYPTOGENIC STROKE; ISCHEMIC-STROKE; POPULATION; EVENTS; SIZE